1997
DOI: 10.1056/nejm199707313370502
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival in Patients with Locally Advanced Prostate Cancer Treated with Radiotherapy and Goserelin

Abstract: Improved survival in patients with locally advanced prostate cancer treated radiotherapy and goserelin Bolla, M.; González González, D.; Warde, P.; Dubois, J.B.; Mirimanoff, R-O.; Storme, G.; Bernier, J.; Kuten, A.; Sternberg, C.; Gil, T.; Collette, L.; Pierart, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
689
3
18

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,420 publications
(726 citation statements)
references
References 12 publications
16
689
3
18
Order By: Relevance
“…Although the final choice of treatment modalities belonged to patients, many patients with locally advanced cancer underwent XRT in our series, as shown in Table 1. Since phase III studies with large cohorts demonstrated that combination therapy with radiation and hormone improved the survival of patients with locally advanced prostate cancer compared with radiation monotherapy, 14,15 we routinely used neoadjuvant LHRH analogue therapy prior to radiation therapy. Our patients received only 66 Gy of radiation, since conformal radiation is not available in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…Although the final choice of treatment modalities belonged to patients, many patients with locally advanced cancer underwent XRT in our series, as shown in Table 1. Since phase III studies with large cohorts demonstrated that combination therapy with radiation and hormone improved the survival of patients with locally advanced prostate cancer compared with radiation monotherapy, 14,15 we routinely used neoadjuvant LHRH analogue therapy prior to radiation therapy. Our patients received only 66 Gy of radiation, since conformal radiation is not available in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…All these biases may have affected previous reports on late rectal toxicity to some extent (Bolla et al, 1997;Sanguineti et al, 2000;Lawton et al, 2001). Contrary to our previous analysis, we tried to minimise the impact of such biases by considering a homogeneously treated group of patients for whom treatment details were available.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have shown some advantage of adding androgen deprivation (AD) to conventional radiotherapy to 66 -70 Gy for prostate carcinoma (Bolla et al, 1997;Lawton et al, 2001;Zagars et al, 1988;Granfors et al, 1998) although improved overall survival was observed only in one (Bolla et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ADT with gonadotropin-releasing hormone agonist or bilateral orchiectomy is the mainstay of treatment for metastatic and recurrent prostate cancer 6 and may be beneficial to men with locally advanced disease. [7][8][9] Although ADT offers important clinical benefits, it is associated with a variety of complications such as hot flushes, anaemia, sexual dysfunction, changing body composition, osteoporosis and fractures, and increased risk for diabetes and cardiovascular diseases. [10][11][12] Some of the complications have negative effects on quality of life assessments, while others may induce serious problems including myocardial infarction and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%